2013
DOI: 10.4049/jimmunol.1202526
|View full text |Cite
|
Sign up to set email alerts
|

Anti–GM-CSF Autoantibodies in Patients with Cryptococcal Meningitis

Abstract: Background Cryptococcal meningitis has been described in immunocompromised patients as well as in those for whom no immune defect has been identified. GM-CSF regulates the function of phagocytes and pulmonary alveolar macrophages, critical elements in cryptococcal control. Methods We performed clinical histories, immunological evaluation, and anticytokine autoantibody screening in 4 current patients with cryptococcal meningitis, and identified and tested 103 archived plasma/CSF samples from patients with cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
211
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 226 publications
(218 citation statements)
references
References 48 publications
4
211
1
2
Order By: Relevance
“…Some of these disorders respond clinically to mechanism-based immunotherapy with IFN-γ or IFN-α (142). Similarly, neutralizing IFN-γ and GM-CSF autoantibodies can underlie adult-onset acquired immunodeficiency characterized by endemic dimorphic fungal (143) and CNS cryptococcal disease (144). Patients with alveolar proteinosis due to impaired GM-CSF signaling develop aspergillosis (145), consistent with murine studies (146).…”
Section: Antifungal Immunity: Lessons From Fungal Disease-associated supporting
confidence: 52%
“…Some of these disorders respond clinically to mechanism-based immunotherapy with IFN-γ or IFN-α (142). Similarly, neutralizing IFN-γ and GM-CSF autoantibodies can underlie adult-onset acquired immunodeficiency characterized by endemic dimorphic fungal (143) and CNS cryptococcal disease (144). Patients with alveolar proteinosis due to impaired GM-CSF signaling develop aspergillosis (145), consistent with murine studies (146).…”
Section: Antifungal Immunity: Lessons From Fungal Disease-associated supporting
confidence: 52%
“…7 (30, 31). As mentioned by Vella et al (30), the tumor Ag MUC-1 could also be the target of Abs in noncancer patients that could have been elicited by infection (56), as formally observed for GM-CSF autoantibodies (57). We cannot completely exclude a link between the anti-CCNB1 humoral response and the memory CCNB1-specific CD4 T cells that we detected in the short-term T cell assays, but there was no correlation between T and B cell responses.…”
Section: Discussioncontrasting
confidence: 37%
“…Patients with C. gattii infection may have subtle defects in immune function (276,279). Marr et al reported IgG2 antibody deficiency in one such patient (280).…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 99%
“…In another PNG study, neither leukocyte antigen class I nor class II phenotypes were associated with C. gattii infection, although there was a trend toward increased susceptibility in patients carrying the human leukocyte antigen B*5601 (275). Recently, high levels of certain anticytokine antibodies (e.g., anti-granulocyte-macrophage colony-stimulating factor [GM-CSF] antibodies) were associated with cryptococcosis in HIV-negative patients (276). These antibodies predispose individuals to opportunistic infections by impairing innate immunity and may be especially relevant among HIV-negative patients in Asia (277,278).…”
Section: Epidemiology Of Human Infectionmentioning
confidence: 99%